Urinary and Plasma Antioxidants in Behavioral Symptoms of Individuals With Autism Spectrum Disorder - Imataka, George; Yui, Kunio; Shiko, Yuki; Kawasaki, Yohei; Sasaki, Hitomi; Shiroki, Ryoichi; Yoshihara, Shigemi (Frontiers in Psychiatry, 2021)
The balance between the antioxidant capacity and oxidative stress-induced free radicals may be crucial the pathophysiological factor in the development of autism spectrum disorder (ASD). We measured the following urinary and plasma biomarker levels of oxidative stress and antioxidants. As urinary biomarkers, 1) hexanoyl-lysine (HEL), which is a new biomarker of oxidative stress, 2) the total antioxidant capacity (TAC), and 3) 8-hydroxy-2′-deoxyguanosine (8-OHdG), as a product of oxidative modifications to DNA; and the plasma levels of 4) the antioxidant protein superoxide dismutase (SOD), which is the crucial defense again oxygen reactive species, and 5) transferrin and 6) ceruloplasmin, which are biomarkers of iron and copper neurotransmission and oxidant-antioxidant systems. We examined the relationship between these urinary and plasma biomarkers and behavioral symptoms in 19 individuals with ASD (mean age, 10.8 ± 5.2 years) and 10 age-matched healthy controls (mean age, 14.2 ± 7.0 years). Behavioral symptoms were estimated using the Aberrant Behavior Checklist (ABC). Urinary TAC levels were significantly lower, whereas urinary HEL levels were significantly increased in the ASD group as compared to the control group. The five ABC subscale and total scores were significantly raised in the autism group than in the control group. The results of a linear regression analysis revealed that plasma SOD levels may be a more accurate predictor of differences in ABC scores between individuals with ASD and control individuals. The present study firstly revealed the important findings that the the cooperation between the urinary antioxidant TAC and plasma SOD levels may contribute to the ABC subscale scores of stereotypy. Urinary TAC activity and antioxidant protein SOD may be associated with incomplete mineral body store, and antioxidant related transcription factor and browning reaction reactions. Consequently, a critical imbalance between TAC urinary levels and plasma SOD levels may be an important contributor to autistic behavioral symptoms.